The fallen [compact disc, unabridged] - Baldacci, David (Baldacci, David. Amos Decker series., 2018)
There's something going on in Baronville, Pennsylvania, that might be the canary in the coal mine for the rest of the country. Decker and Jamison must pull out all the stops to solve their latest case.